Digitally Disposed and Compromised. - Birringer, Johannes (Contemporary Music Review, 2025)
Music technology and electronic music performance, dance, interactive design and movement animation (visual and sonic) have enjoyed challenging partnerships for some decades now, but the constant evolution of software capabilities and multimodal design, in the current context of so-called immersive performance, has also raised critical questions about embodiment and the digital disposition or rendition of dancers or performers whose gestures and 'movement data' are captured and transmuted. This paper's investigation of older and newer dimensions of interactive technological design of performance was motivated by two recent concerts (Habiter (avec) Xenakis, an Augmented Reality recital at Enghien-Les-Bains' Centre des Arts; Anti-Body, by Alexander Whitley Dance Company, Sadler's Wells) which seemed to point in a direction that requires careful attention—also in the controversial context of AI and algorithmic fungibility of digitised objects—in order to parse some of the uses of technological constraints and operational processes which the author here bemoans as dispossession and disintegration of the performers' physical presence in a stage concert.